TB among refugees from Ukraine in European countries - G. de Vries; J.P. Guthmann; B. Häcker; B. Hauer; K. Nordstrand; A. Nowinski; H. Soini (IJTLD Open)
BACKGROUND: Since the Russian Federation’s invasion of Ukraine, millions of refugees have moved to neighbouring European countries. We assessed the burden of TB in these refugees and surveyed screening approaches. METHODS: We conducted a survey among 30 European Union/European Economic Area and 13 other European countries, requesting population data on migrant residents and refugees with country of birth (COB) Ukraine, the number of TB notifications among people with COB Ukraine and countries’ screening policies for refugees from Ukraine. RESULTS: In 2021, the number of migrants born in Ukraine was 1.7 million in the 34 responding countries, and increased with 5.2 million refugees from Ukraine to 6.9 million in 2022. These countries notified 207 TB cases in people with COB Ukraine in 2021 (TB notification rate 12.0/100,000) and 887 in 2022 (TB notification rate 12.8/100,000), of which 228 (26%) had multidrug-resistant/rifampicin-resistant TB (MDR/RR-TB). TB notification rates were higher in countries advising screening for all (16.9/100,000) or specific groups of refugees from Ukraine (14.7/100,000) compared to those without screening (7.2/100,000). CONCLUSION: TB rates found in people from Ukraine were lower than the expected rate of 44 per 100,000, but higher in host countries recommending screening. Our study underscores the need for adequate TB health services for refugees from Ukraine to ensure tailored diagnosis and treatment, especially for MDR/RR-TB.